A Revival of the Private Rental Sector of the Housing Market? Lessons from Germany, Finland, the Czech Republic and the Netherlands - de Boer, Rik (OECD Economics Department Working Papers, 2014)
This Working Paper studies ways to stimulate the private rental sector (PRS) of the housing market - and compares experiences with policies and reforms in Germany, the Netherlands, Finland and the Czech Republic. Although in many countries the PRS has decreased in importance since the Second World War, there are signs of a growing importance and possible 'revival' of the PRS. A well-functioning PRS and neutrality in housing policies can improve the functioning of the housing market - by promoting residential mobility, increasing housing options for households and generating competitive supply and affordable prices. The PRS can have positive effects on the economy and labour mobility and reduce inefficiencies and risks of owner-occupied and social housing. Trade-offs between goals in housing policies, and regulatory impediments to a level playing field between segments of the housing market (owner-occupancy, social rental, private rental) are analysed. The article outlines policy options in promoting a well-functioning PRS: lessons are drawn on tenancy security, rent-setting regulations, social housing, demand subsidies, fiscal measures for rental and owner-occupied housing and barriers for PRS supply. Experiences from the countries show that it is hard to create a level playing field - there are inefficiencies in all four countries. Nonetheless, there are many positive experiences of stimulating the PRS: reforms in Finland and the Czech Republic stimulated the PRS to become a competitive and important part of the housing market, and Dutch policies are adapted to stimulate a level playing field. The 'resilience' of the German housing system during the economic crisis shows that the large PRS and tenure neutrality have important stabilising effects on the German economy